2008
DOI: 10.1007/s00248-008-9390-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant Responses to Drought Stress and Exogenous ABA Application are Modulated Differently by Mycorrhization in Tomato and an ABA-deficient Mutant (Sitiens)

Abstract: The aims of the present study are to find out whether the effects of arbuscular mycorrhizal (AM) symbiosis on plant resistance to water deficit are mediated by the endogenous abscisic acid (ABA) content of the host plant and whether the exogenous ABA application modifies such effects. The ABA-deficient tomato mutant sitiens and its near-isogenic wild-type parental line were used. Plant development, physiology, and expression of plant genes expected to be modulated by AM symbiosis, drought, and ABA were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 70 publications
8
69
0
2
Order By: Relevance
“…Previous work also studied the relationship between tomato and AM fungi under WS (Dell'Amico et al, 2002;Subramanian et al, 2006;Aroca et al, 2008;Wang et al, 2014;Ruiz-Lozano et al, 2016). The discrepancy among data already available could be due to the use of different plant varieties and fungal species/isolates as well as to different growth and drought stress conditions (Augé et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work also studied the relationship between tomato and AM fungi under WS (Dell'Amico et al, 2002;Subramanian et al, 2006;Aroca et al, 2008;Wang et al, 2014;Ruiz-Lozano et al, 2016). The discrepancy among data already available could be due to the use of different plant varieties and fungal species/isolates as well as to different growth and drought stress conditions (Augé et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Although the role of AM fungi in plant WS tolerance has been well reported for several plant-AM fungus combinations, the underlying molecular mechanisms are still to be elucidated. The regulation of several genes putatively involved in the response to WS, such as aquaporin genes (Porcel et al, 2006), a gene (P5CS) encoding a rate-limiting enzyme of Pro synthesis (Porcel et al, 2004), and a gene (NCED) encoding a key enzyme in the abscisic acid (ABA) biosynthesis pathway (Aroca et al, 2008), has already been reported for AM-colonized plants under drought conditions. A potential water transport via AM fungus to the host plant has been suggested on the basis of the gene expression profiles for two functionally characterized fungal aquaporin genes, thus supporting the existence of a direct AM fungus involvement in plant tolerance to drought (Li et al, 2013a(Li et al, , 2013b.…”
mentioning
confidence: 95%
“…Hydrogen peroxide content was determined according to Patterson's method (Patterson et al 1984) with slight modifications as described by Aroca et al (2008). Fivehundred milligrams of fresh leaves were homogenized in a cold mortar with 5 mL 5 % TCA containing 0.1 g of activated charcoal and 0.1 g PVPP.…”
Section: Hydrogen Peroxide (H 2 O 2 ) Contentmentioning
confidence: 99%
“…AM fungi may also directly improve plant water relations by increasing root water absorption and leaf water potential, regulating transpiration rate (Augé 2001(Augé , 2004, and enhancing photosynthetic rates (Subramanian and Charest 1995). The underlying mechanisms for the aforementioned effects of mycorrhiza on water uptake may be the changes in plant drought-related gene expression, such as genes encoding aquaporins Porcel et al 2006;Li et al 2013) or genes encoding 9-cis-epoxycarotenoid dioxygenase (NCED), the key enzyme in the biosynthesis of abscisic acid (ABA) (Aroca et al 2008). The latter authors also reported that Rhizophagus intraradices significantly enhanced the expression of nced and other plant genes encoding plasma membrane intrinsic proteins (PIPs) in roots and resulted in a remarkable increase of shoot dry weight under drought conditions.…”
Section: Introductionmentioning
confidence: 99%